Bridging Ethics and Education: Crafting Solutions to Address the Threads of Bullying in Indonesia - Marhaendra, Gregory Yehezkiel (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2024)
Bullying in educational settings has become a significant global issue, exacerbated by the rise of cyberbullying and juvenile delinquency, particularly in Indonesia. The study employs a qualitative approach and literature review to investigate the impact of the curriculum on shaping ethical values and character among students. By focusing on ethical education, particularly the principles of individualism and collectivism, and incorporating deontological and virtue ethics, this research proposes a holistic strategy for addressing bullying. It argues that understanding and integrating these ethical dimensions into school curricula can foster a supportive environment that mitigates bullying and promotes moral development. Additionally, the study underscores the importance of moral philosophy in healing the trauma caused by bullying. It advocates applying ethical principles such as justice, compassion, and empathy to support affected students, helping them overcome trauma and build resilience. The study advocates for applying moral philosophies to help students navigate complex social dynamics, thereby enhancing their emotional well-being and contributing to a more empathetic and just educational environment.